2005
DOI: 10.1111/j.1526-100x.2005.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Restoration as a Means of Controlling Non‐Native Fish in a Mojave Desert Oasis

Abstract: Non-native fish generally cause native fish decline, and once non-natives are established, control or elimination is usually problematic. Because non-native fish colonization has been greatest in anthropogenically altered habitats, restoring habitat similar to predisturbance conditions may offer a viable means of non-native fish control. In this investigation we identified habitats favoring native over non-native fish in a Mojave Desert oasis (Ash Meadows) and used this information to restore one of its major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…In the Grande Briere Mottibre, the invasion of natural habitats (grasslands) by reed beds during the last century has substantially altered ecosystem function (Eybert et al 1998). This habitat modification is Scoppettone et al (2005) demonstrated that habitat restoration could be valuable to control non-native fish species. Consequently, we propose that managers continue the systematic mass removal but in conjunction with natural habitat restoration to more efficiently regulate the black bullhead population in the Grande Britre Mottiere marsh.…”
Section: Resultsmentioning
confidence: 95%
“…In the Grande Briere Mottibre, the invasion of natural habitats (grasslands) by reed beds during the last century has substantially altered ecosystem function (Eybert et al 1998). This habitat modification is Scoppettone et al (2005) demonstrated that habitat restoration could be valuable to control non-native fish species. Consequently, we propose that managers continue the systematic mass removal but in conjunction with natural habitat restoration to more efficiently regulate the black bullhead population in the Grande Britre Mottiere marsh.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, feedbacks between individual threats may result in potential unintended Environmental Management consequences from restoration, such as restored flow conditions benefiting non-native species (Marks et al 2010). Although examples of flow regime restoration leading to the reestablishment of native species are apparent in the literature (e.g., Scoppettone et al 2005;Kiernan et al 2012), both positive and negative ecological feedbacks have been observed and predicted (Reich et al 2010). The restoration of a more natural flow regime in New Zealand streams is predicted to allow non-native brown trout Salmo trutta to colonize areas that provide refuges for the native roundhead galaxias Galaxias anomalus potentially leading to the species' extirpation (Leprieur et al 2006).…”
Section: Invasive Speciesmentioning
confidence: 98%
“…Restoring natural flow regimes, including periods of high and low flows, may help reduce populations of invasive aquatic species. In the western United States, the success of non-native fish species can be reversed, in part, by restoration of natural flow regimes (Marchetti & Moyle 2001;Scoppettone et al 2005). …”
Section: Changes In Control Strategies and Their Initiationmentioning
confidence: 99%